The Impact of Academic Counseling on Perceived Classroom Assessment with the Mediating Role of Students’ Autonomy Support - Bi Gham, Fahimeh; Pali , Samira (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate the effect of academic counseling on perceived classroom assessment, with a specific focus on the mediating role of students’ autonomy support in the educational setting. The research employed a descriptive-correlational design with an applied purpose. The statistical population included all first-grade middle school students (both male and female) in Rudsar County during the academic year 2024–2025. A total of 322 students were selected using stratified random sampling based on Krejcie and Morgan’s table. Data were collected using three standardized instruments: the Academic Counseling Questionnaire by Wen et al. (2018), the Autonomy Support Questionnaire by Legate et al. (2012), and the Perceived Classroom Assessment Questionnaire by Al-Kharusi et al. (2009). The validity and reliability of the instruments were confirmed through factor analysis and Cronbach’s alpha. Data analysis was performed using descriptive statistics, Kolmogorov–Smirnov test for normality, and structural equation modeling (SEM) using SmartPLS software. The results indicated that academic counseling had a significant direct positive effect on students’ perceived classroom assessment (β = 0.413, t = 10.813, p < 0.05). Academic counseling also positively predicted autonomy support (β = 0.336, t = 7.083, p < 0.05), which in turn significantly influenced perceived classroom assessment (β = 0.119, t = 2.412, p < 0.05). The mediation analysis confirmed that autonomy support partially mediated the relationship between academic counseling and perceived classroom assessment, with an indirect effect coefficient of 0.040 (t = 2.209, p < 0.05). The findings underscore the importance of academic counseling as a multidimensional intervention that not only directly enhances students’ perception of classroom assessment but also does so indirectly through the development of autonomy. This highlights the need for autonomy-supportive counseling practices to foster meaningful learning environments.